Upaya Meningkatkan Minat Belajar Bahasa Arab melalui Media Gambar - Cahyono, Dedi Dwi; Mustofa, Nurul Hadi; Fatoni, Ahmad; Gufron, Anik (Lembaga Yasin AlSys, 2022)
The teaching and learning process cannot be separated from the role of the media in it, because learning media is an integral part of the educational process in schools. The position of teaching media is in the component of the teaching and learning process as an effort to enhance teacher-student interaction and student interaction with their environment. There are various methods of teaching, one of which is visual media (Pictures). The method used in this research is Library Research, which is a series of activities related to the methods of collecting library data, reading and taking notes and processing research materials. The results of this study concluded that the teaching and learning process cannot be separated from the role of the media, because learning media is an integral part of the educational process. . Some of the factors that cause failure in learning Arabic include factors from students who consider Arabic a difficult subject, and their lack of confidence in communicating.